PRODUCTION AND CHARACTERIZATION OF CHITINASE ENZYMES FROM SULILI HOT SPRING IN SOUTH SULAWESI, Bacillus sp. HSA,3-1a - Hasnah Natsir; Abd. Rauf Patong; Maggy Thenawidjaja Suhartono; Ahyar Ahmad (Indonesian Journal of Chemistry, 2010)
Chitinase is an extracellular enzyme which is capable in hydrolyzing insoluble chitin to its oligomeric and monomeric components. The enzyme produced by thermophilic bacteria was screened and isolated from Sulili hot spring in Pinrang, South Sulawesi, Indonesia. The gram positive spore forming rod shape bacteria was identified as Bacillus sp. HSA,3-1a through morphological and physiological analysis. The production of chitinase enzyme was conducted at various concentration of colloidal chitin at a pH of 7.0 and a temperature of 55 °C. The bacteria optimally was produced the enzyme at a colloidal chitin concentration of 0.5% after 72 h of incubation. The optimum temperature, pH and substrate concentration of chitinase were 60 °C, 7.0 and 0.3%, respectively. The enzyme was stable at a pH of 7.0 and a temperature of 60 °C after 2 h of incubation. The chitinase activities was increased by addition of 1 mM Mg2+, Ca2+ and Mn2+ ions, whereas the activities were decreased by 1 mM Co2+, Fe2+ andZn2 ions. The molecular weight of the crude enzyme was determined using SDS-PAGE analysis. Five protein fractions were obtained from SDS-PAGE, with MWs of 79, 71, 48, 43 and 22 kDa.